Mechanism of Acupuncture Therapy on RANKL/OPG Signaling Pathway to Regulate Bone Metabolism Balance in Osteoporosis Model Rats - Qin YIN; Hong PAN; Xiaojuan DING; Xiaoguang QIN; Xiaorong GUO (康复学报)
Objective:To explore the effect of acupuncture therapy on receptor of activator of nuclear factor-k B ligand(RANKL)/osteoprotegerin(OPG)signaling pathway in ovariectomized rats, and to analyze its mechanism of regulating bone metabolism balance.Methods:A total of 60 SPF female Wistar rats were randomly divided into the blank group, the model group, the estradiol group and the acupuncture group, with 15 rats in each group. Except the blank group, the other three groups were ovariectomized to establish osteoporosis model. The rats in the blank group and the model group were given 0.9%NaCl solution for 50 μg/(kg·d)by gavage, the estradiol group was given estradiol valerate 50 μg/(kg·d)by gavage, the acupuncture group was given electroacupuncture at Shenshu, Sanyinjiao, Guanyuan, Zusanli acupoints with stimulation intensity of 2 mA, frequency of 2 Hz, 15 min/time, once a day. Enzyme linked immunosorbent assay(ELISA)was used to analyze bone specific alkaline phosphatase(BALP), cterminal type I collagen telopeptide(CTX-I), core-binding factor-α1(CBF-α1), procollagen type I amino-terminal peptide(PINP), osteocalcin(OC)of the four groups;The relative bone volume fraction(BV/TV), trabecular number(Tb. N), trabecular bone thickness(Tb. Th), connective density(Conn. D), trabecular bone separation(Tb. Sp), structural model index(SMI)were analyzed by Micro-CT;TUNEL method was used to detect apoptosis of distal femur cells in four groups;Western blot and RT-PCR method were used to detect the protein expression levels of RANKL, OPG mRNA in femur and hypothalamus in four groups.Results:①BMD and bone metabolism markers: compared with the blank group, BMD, BALP, CBF-α1, CTX-I, PINP and OC in the model group were significantly decreased(P<0.05). Compared with the model group, BMD, BALP, CBF-α1, CTX-I, PINP and OC in the acupuncture group were significantly increased(P<0.05).②Trabecular microstructure: compared with the blank group, BV/TV, Tb. N, Tb. Th, Conn. D in the model group were significantly decreased, while Tb. Sp, SMI were significantly increased(P<0.05). Compared with the model group, BV/TV, Tb. N, Tb. Th and Conn. D in the acupuncture group were significantly increased, while Tb. Sp and SMI were significantly decreased(P<0.05).③Apoptosis of distal bone cells: compared with the blank group, the number of apoptotic cells in the model group increased significantly;compared with the model group, the number of apoptotic cells in the distal femur of the estradiol group and the acupuncture group decreased significantly.④OPG and RANKL mRNAand protein expression in hypothalamus and femur: compared with the blank group, OPG mRNA and protein expression in hypothalamus and femur of the model group were significantly decreased, while RANKL mRNA and protein expression were significantly increased(P<0.05);compared with the model group, the expression of OPG mRNA and protein in hypothalamus and femur of the acupuncture group were significantly increased, while the expression of RANKL mRNA and protein were significantly decreased(P<0.05). Conclusion:Acupuncture therapy can improve bone density, regulate bone metabolism level and improve bone trabecular microstructure in OP model rats, its mechanism may be related to the regulation of RANKL/OPG signal pathway.